Scientometric analysis of energetic ecology: primary production of aquatic macrophytes - DOI: 10.4025/actascibiolsci.v31i4.5139 - Lolis, Solange de Fátima; Sanches-Marques, Angela Maria Marques; Arruda Reis, Sebastiana Lindaura; Benedito, Evanilde (Acta Scientiarum. Biological Sciences, 2009)
The objective of this work was to perform a temporal quantitative analysis, using the scientometric technique, considering the number of citations that the terms Primary Production of Aquatic Macrophytesand Energetic Ecology received in a 50-year period (1956 to 2006). The study related 189 papers published in 26 magazines. It was verified that researchers of several nationalities are working on the proposed themes, with a predominance of those from developed countries (USA and Germany). In Brazil, production on these themes, although small, coincides with the results obtained for other themes analyzed using the same research technique. This fact indicates that greater efforts should be made in the search for more intense scientific production in the country, in the different areas of knowledge, especially in the object of this study